EFEKTIFITAS KEPEMIPINAN KEPALA SEKOLAH DALAM MENINGKATKAN PRESTASI GURU DI SMK PUTRA ANDA BINJAI - Neliwati Neliwati; Rahmad Rinaldi; Mutiara Ritonga (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
Purpose of this paper is to see the effectiveness of the principal's leadership in improving teacher achievement at SMK Putra Anda Binjai. This research took place at SMK Putra Anda Binjai which is located on JL. WR Mongonsidi No. 22, Satria Village, Binjai City Regency. The research was conducted on June 9, 2021. The subject of this research is the school owner who acts as a leader at SMK Putra Anda Binjai. The data collection technique is by interview. The results of this study are: (1). The leadership behavior at SMK Putra Anda Binjai in teacher performance management is to always provide direction to teacher activities and student activities at school, provide motivation to teachers in carrying out learning at school, always communicate well with all teachers at school, be disciplined and firm in every decision making at school, and Create a family relationship in the school both to teachers, students and other staff. (2). The influence on teacher performance in schools can be seen from four aspects, namely discipline aspects, religious aspects, cooperation aspects, leadership aspects. (3). The forms of principal performance management strategies in improving teacher performance are 1) strategies for providing allowances/salaries/rewards, 2) paying attention to teachers, 3) providing teacher training in honing teacher skills, 4) empowering teachers in decision making.